2018
DOI: 10.3389/fimmu.2018.01637
|View full text |Cite
|
Sign up to set email alerts
|

T Follicular Helper Cells in Autoimmune Disorders

Abstract: T follicular helper (Tfh) cells are a distinct subset of CD4+ T lymphocytes, specialized in B cell help and in regulation of antibody responses. They are required for the generation of germinal center reactions, where selection of high affinity antibody producing B cells and development of memory B cells occur. Owing to the fundamental role of Tfh cells in adaptive immunity, the stringent control of their production and function is critically important, both for the induction of an optimal humoral response aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
141
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 233 publications
(296 reference statements)
3
141
1
1
Order By: Relevance
“…Considering that Tfh cells specialized in providing help to B cells are essential for GC formation, affinity maturation, and the development of memory B cells 27 , whereas Tfr cells are critical for controlling Tfh cell:B cell interaction 29,30 , dLN cells were also examined for their frequency. To identify these cells, conventional Foxp3-CD4+ cells and Foxp3+ CD4+ cells encompassing predominantly regulatory T cells 44 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that Tfh cells specialized in providing help to B cells are essential for GC formation, affinity maturation, and the development of memory B cells 27 , whereas Tfr cells are critical for controlling Tfh cell:B cell interaction 29,30 , dLN cells were also examined for their frequency. To identify these cells, conventional Foxp3-CD4+ cells and Foxp3+ CD4+ cells encompassing predominantly regulatory T cells 44 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional CD4+ T cells differentiate into Tfh cells through a specific pathway that terminates in the high expression of the B-cell follicle homing chemokine (C-X-C motif) receptor 5 (CXCR5) and their localization to the GCs 27,28 . Thus, the stringent control of Tfh cell generation and function is critically important for the induction of an optimal humoral response against thymus-dependent antigens and the prevention of self-reactivity, alike 29,30 . Consistently, deregulations of Tfh response can contribute to the production of pathogenic autoantibodies, and thereby the promotion of autoantibody-mediated autoimmune diseases, including RA 29,30 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been subsequently shown these cells have an even larger role in host immunocompetence. Specifically, it has been shown that abnormal differentiation and hyperfunction of T fh cells can cause an immune imbalance in a host (Ma and Deenick 2014;Ueno et al 2015;Varricchi et al 2016;Gensous et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tfh cells can promote antigen-specific B cell activation, germinal center formation and humoral responses [12,13]. In addition, Tfh cells are involved in the pathogenic process of some autoimmune diseases [14-16] and participate in defensing against parasite infection [17,18]. Indeed, increased frequency of Tfh cells is detected in rodent with S. japonicum infection and Tfh cells activated by ICOS + macrophages infiltrate into the liver and enhance the liver injury in mice infected with S. japonicum [19].…”
Section: Introductionmentioning
confidence: 99%